Analysis of Company Value through Financial Performance as a Mediating Variable : JEL Classification: G32, G34, L25, M41, C23 - Jason Jason; Hartono Hartono; Hadi Santoso (Journal La Bisecoman, 2026)
This study examines the relationship between CEO nationality, capital structure, and firm activity on firm value, both directly and indirectly through financial performance. The sample consists of primary consumer goods companies listed on the Indonesia Stock Exchange during 2018–2024, resulting in 406 observations analyzed using Stata 17. The results show that CEO nationality, firm activity, and financial performance positively affect firm value, while capital structure has no direct effect. These findings suggest that the presence of foreign CEOs, effective firm activities, and strong financial performance enhance investors’ perceptions of firm value. Further results indicate that CEO nationality and firm activity do not affect financial performance, whereas capital structure negatively affects financial performance, implying that higher debt usage may increase financial burdens and reduce financial performance. Moreover, financial performance fully mediates the relationship between capital structure and firm value but does not mediate the influence of CEO nationality or firm activity on firm value. Overall, this study contributes to the literature by emphasizing the important role of financial performance in explaining firm value.